Trade Special Issue: Foreword - Kolsky Lewis, Meredith (Victoria University of Wellington Law Review, 2006)
This foreword introduces four articles featured in this volume of the Victoria University of Wellington Law Review, all of which address trade law from diverse angles: Oliver Delvos "WTO Disciplines and Fisheries Subsidies – Should the SCM Agreement Be Modified?" (2005) 37 VUWLR 341; Thomas A Faunce, Kellie Johnston, and Hilary Bambrick "Trans-Tasman Therapeutic Products Authority: Potential AUSFTA Impacts on Safety and Cost-Effectiveness Regulation for Medicines and Medical Devices in New Zealand" (2005) 37 VUWLR 365; Jane Kelsey "Free Trade Agreements – Boon or Bane: Through the Lens of PACER" (2005) 37 VUWLR 391; and Nicholas Whittington "Reconsidering Domestic Sale of Goods Remedies in Light of CISG" (2005) 37 VUWLR 421.